Circular polarization in the optical afterglow of GRB 121024A - Wiersema, K.; Covino, S.; Toma, K.; van der Horst, A.; Varela, K.; Min, M.; Greiner, J.; Starling, R.; Tanvir, N.; Wijers, R.; Campana, S.; Curran, Peter; et al. (Nature Publishing Group, 2014)
Gamma-ray bursts (GRBs) are most probably powered by collimated relativistic outflows (jets) from accreting black holes at cosmological distances. Bright afterglows are produced when the outflow collides with the ambient medium. Afterglow polarization directly probes the magnetic properties of the jet when measured minutes after the burst, and it probes the geometric properties of the jet and the ambient medium when measured hours to days after the burst. High values of optical polarization detected minutes after the burst of GRB 120308A indicate the presence of large-scale ordered magnetic fields originating from the central engine (the power source of the GRB). Theoretical models predict low degrees of linear polarization and no circular polarization at late times, when the energy in the original ejecta is quickly transferred to the ambient medium and propagates farther into the medium as a blast wave. Here we report the detection of circularly polarized light in the afterglow of GRB 121024A, measured 0.15 days after the burst. We show that the circular polarization is intrinsic to the afterglow and unlikely to be produced by dust scattering or plasma propagation effects. A possible explanation is to invoke anisotropic (rather than the commonly assumed isotropic) electron pitch-angle distributions, and we suggest that new models are required to produce the complex microphysics of realistic shocks in relativistic jets.